Tree diametric-species diversity is affected by human impact in old Scots pine dominated forest in boreal Fennoscandia - de Quesada Alzamora, Gonzalo E; Kuuluvainen, Timo (Forest Ecosystems, 2020)
Background Forest structural and compositional variability is of fundamental importance for forest ecosystem functioning and species diversity. The purpose of this research was to examine how human impact has affected the compositional-structural diversity of mature pine-dominated boreal forest in boreal Fennoscandia. For this a new approach was used, based on the classification of tree sizes by the diameter at breast height (dbh) and tree species, resulting in a new variable, the diametric-species, the variation of which describes the compositional-structural diversity of the forest. This variable was used to compare the structural-compositional diversity among three forest classes with different degree of human influence, using rarefaction as the main tool of analysis, complemented by analyses based on common diversity indices. Results The results showed that the near-natural forest was the most diverse and the managed forest the least diverse. On the other hand, the diversity of near-natural and selectively logged forests were similar, suggesting that selectively logged forests are equal to the natural forest in their compositional-structural diversity. The analysis solely on tree species showed no significant differences among the forest classes of different human impact. The Shannon diversity index showed no significant difference between the forest classes for the diametric-species and tree species classifications only, but the Simpson index signaled a slight difference between the selectively logged and managed forest classes for the diametric-species classification. Furthermore, the Sorensen index detected a difference among forest classes in the diametric-species classification. Conclusions Forest utilization had an adverse impact on forest compositional-structural diversity of mature Scots pine forests. The analysis also shows that the novel approach based on diametric-species classification could be a useful tool for forest diversity analysis and comparison, especially in species-poor forests such as ...